ChemInform Abstract: Suzuki—Miyaura Reactions of Halospirooxindole Derivatives. Issue 39 (September 2015) - El Bouakher, Abderrahman; Allouchi, Hassan; Abrunhosa‐Thomas, Isabelle; Troin, Yves; Guillaumet, Gerald
Abstract Based on the regioselective mono‐ and dibromination of spirofuroindoline (I) an efficient synthesis of mono‐ and diarylated products is developed.